The types of idiom in the addams family movie - Panji, I Gusti Ngurah; Santika, I Dewa Ayu Devi Maharani; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2022)
This study is aimed to analyze the type of idiom in The Addams Family Movie. The data source of this study was taken from The Addams Family Movie transcript. This research used a descriptive qualitative method in analyzing the data. The theory of type of idioms by Seidl & McMordie (1988) was used to analyze the types of idioms found in The Addams Family Movie. As a result there are 9 pieces of data that contain idiom expression. They belong to 4 phrasal verb type (4 data) and 5 key words with idiomatic uses type (5 data).